2014
DOI: 10.4028/www.scientific.net/amm.543-547.4194
|View full text |Cite
|
Sign up to set email alerts
|

Research of Human Errors in Maritime System

Abstract: The importance of the human element in maritime safety is increasingly being recognized by the shipping and offshore communities. In this paper, the author is going to make an introduction of the application of the human factors in maritime technology in recent years, and talk about the failures of situation awareness which are exceedingly common and need to be handled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The research questions were formulated from the relevant motifs identified from the qualitative analysis of data and theory of planned behaviour [20,21]; they were the foundation of the determining of notions and beliefs of data planning and management. The collection of related empirical data suitable for authentication required appropriation of terminology and definition of bounds.…”
Section: / Design Of Questionnairementioning
confidence: 99%
“…The research questions were formulated from the relevant motifs identified from the qualitative analysis of data and theory of planned behaviour [20,21]; they were the foundation of the determining of notions and beliefs of data planning and management. The collection of related empirical data suitable for authentication required appropriation of terminology and definition of bounds.…”
Section: / Design Of Questionnairementioning
confidence: 99%
“…Risky occupations have a safety management system (SMS) in order to monitor and react to how the safety level changes, and to enhance safety by improving the relevant aspects of the sociotechnical work environment. System design, work-environment, personnel readiness and interpersonal and organizational factors should be considered in order to maintain safety on maritime vessels (Chauvin, 2011;Ding, Han, Li, & Deng, 2014).…”
Section: : Introductionmentioning
confidence: 99%
“…Organisations with a high level of risk have a safety management system in order to monitor and react to how the safety level changes, and to enhance safety by improving relevant aspects of the sociotechnical work environment. System design, work-environment, personnel readiness and interpersonal and organisational factors should be considered in order to maintain safety on maritime vessels (Chauvin, 2011;Ding et al, 2014).…”
Section: Introductionmentioning
confidence: 99%